The Effectiveness of social media in enhancement of news consumption - Shahwar, Dure; Afaq ahmad (University of Wah Journal of Social Sciences, 2024)
ABSTRACT The emergence of social media has altered the way people consume news, leading to a greater sense of confidence in accessing news that aligns with their interests and goals. This research examines the constraints of social media as a news source, while also evaluating the impact of platforms like Twitter, Facebook, and Instagram on the field of journalism and the way people engage with news. Social media platforms serve as an alternative means of obtaining information, as users are not reliant on television and mass media to report on events. Users can engage in discussions and share news on the platforms, which enhances the way news is consumed, moving from passive to active. In addition to that, the essay also analyzes the problems that can occur when using a social media platform as a source of news. The dissemination of false information and misleading content, sensationalism, and the echo chamber effect are likely the most significant of these. These concerns lead to questions about the reliability of news shared and viewed on social media platforms. Furthermore, the manner in which companies create their Facebook pages and the content that appears on them has altered the way news is interpreted. Nonetheless, social media still works well for the improvement of news reading patterns, especially among younger generations